Propuesta de un sistema de control interno, al área de inventarios en la empresa Concali Colombia S.A.S. (2023)
The present research derived from a descriptive study aims to analyze the internal control developed in the area of inventories of the company Concali SAS, through the different techniques of field work such as the investigation, observation and application of surveys, the degree of effectiveness of the existing controls is evidenced before the risks to which it is exposed, assessing the residual risk that the entity tolerates and in this way suggest improvement plans that strengthen the activities related to inventory management.